Effect of supplementation of BS4-enzyme levels in rice-bran based rations on performance of growing PMp broiler duck - Maijon Purba; Arnold Parlindungan Sinurat (Jurnal Ilmu Ternak dan Veteriner, 2018)
The purpose of enzymes supplementation in feeds is to improve nutrient digestibility through degradation of anti-nutrition and crude fiber, which are commonly found in rice bran. The aim of the study was to see performance response of PMp broiler ducks to the supplementation of BS4-enzyme levels in rice-bran based rations. Two hundred and twenty four day-old ducks were allocated to 8 dietary treatments with 4 replicates, consisted of 7 ducks in each replicate. The composition of the feed treatments arranged as follows: T1 to T4 were rations with 30% of rice bran content with enzyme levels of 0, 50, 100, and 150 Unit/kg rice bran respectively. T5 to T8 were rations with 60% of rice bran content with the same enzyme levels as for T1 to T4 treatments. The ducklings were subjected to the treatments for the first four weeks. The variables observed were feed intake, weight gain and FCR. The results showed that the supplementation of BS4-enzymes on rice-bran based rations significantly affected (P<0.05) feed intake and FCR, but not for weight gain (P>0.05). The most effective rations for feed consumption and FCR of PMp broiler duck were obtained on T4 treatment resulting in the highest body weight gain of 998 g/bird and lowest FCR of 2,64. It was concluded that the supplementation of 150 Unit/kg of BS4 enzyme in 30% rice-bran diet was the best combination level to be implemented in feeding PMP broiler ducks for the first four weeks period.